Sensory Vocabulary in Multimodal Digital Brand Storytelling (Based on the English-Language Websites and Social Media - Кір’якова, Дар’я Дмитрівна (Київський національний університет імені Тараса Шевченка, 2025)
This article investigates the use of sensory vocabulary within multimodal digital brand storytelling, analysing how linguistic choices, in conjunction with visual, auditory, and interactive elements, contribute to brand perception and consumer engagement. Employing a mixed–methods approach, we combine multimodal and contextual discourse analysis with quantitative data and empirical observations of brand websites and social media content. We have analysed how leading brands across industries, including spheres such as technology, cosmetics, and food and beverage, utilise sensory language, in conjunction with visual, auditory, and interactive modes, to construct compelling digital narratives. Findings reveal that the effective integration of sensory vocabulary significantly enhances brand perception by creating immersive and emotionally resonant experiences, tailored to specific product offerings and brand identities. The article reveals usage of distinct sensory strategies, demonstrating the importance of contextual factors and the complex interplay of multimodal elements. Furthermore, the study underscores the emotional impact of sensory language, particularly in fostering brand loyalty and consumer engagement, highlighting the connection between tactile descriptions and emotional narratives. This research contributes to a deeper understanding of digital brand communication, offering insights for strategic sensory storytelling and digital branding, and provides a framework for future research into the evolving landscape of digital sensory marketing.

У цій статті досліджується використання сенсорної лексики в мультимодальному цифровому сторітелінгу брендів, аналізується, як лінгвістичний вибір у поєднанні з візуальними, аудіо та інтерактивними елементами сприяє сприйняттю бренду та залученню споживачів. Використовуючи змішаний підхід, ми проаналізували, як провідні бренди в різних галузях використовують сенсорну мову в поєднанні з візуальними, аудіо та інтерактивними елементами для побудови переконливих цифрових наративів. Результати дослідження показують, що ефективна інтеграція сенсорної лексики значно покращує сприйняття бренду, створюючи захоплюючий та емоційно резонансний досвід, адаптований до конкретних продуктових пропозицій та ідентичності бренду. Це дослідження сприяє глибшому розумінню цифрової бренд–комунікації, пропонуючи ідеї для стратегічного сенсорного сторітелінгу та цифрового брендингу, а також створює основу для майбутніх досліджень у сфері цифрового сенсорного маркетингу, що еволюціонує.
Сенсорна лексика в мультимодальному цифровому сторітелінгу брендів (на матеріалі англомовних веб-сайтів та соціальних мереж
Keywords: sensory vocabulary; sensory marketing; multimodality; storytelling; digital communication; narrative; social media; marketing; сенсорна лексика; сенсорний маркетинг; мультимодальність; сторітелінг; цифрова комунікація; наратив; соціальні медіа; маркетинг